Effect Of Adding Indium And Zinc Alloying Elements To Creep Behavior Of Sn-0.7cu Solder Alloy - Tan, Joo Kean (Universiti Sains Malaysia, 2017)
For several years, Sn-0.7Cu solder has been used in electronic packaging industries to replace the Sn-Pb solder in order to reduce the negative impact of lead to the environment and human health. However, the relatively poor wettability and mechanical properties of Sn-Cu solder alloys has raised reliability concern in the actual application. Micro-alloying has been reported as one of the most effective approaches to improve the properties of solders by minor additions of alloying elements to the alloy system. In this project, 0.5 and 1.0 wt.% Zn had been added to the Sn-0.7Cu-1.0In base solder, and the effect of alloying elements on thermal behaviour, solderability, microstructure and intermetallic compounds (IMCs) observation, mechanical properties, and effect of isothermal aging on shear strength have been studied. The best performing solder is one with 0.5 wt.% Zn solder. The wettability, hardness, reflowed and aged shear strength were found to be highest amongst the solder samples. The melting temperature of solder increased with the amount of Zn content. However, the pasty range and thickness of IMC layer decreased with increasing of Zn. From SEM observation, In and Zn have been observed to dope into the Cu6Sn5 forming Cu6(Sn,Zn)5 and Cu6(Sn,In)5. Besides, formation of Cu-Zn compound became favourable when 1.0 wt% Zn is added. For creep test, Sn-0.7Cu-1.0In-1.0Zn has the highest creep resistance among the sample due to the presence of Zn-rich second phase particles which effectively impeding the dislocation movement.